2006
DOI: 10.1186/1471-2407-6-225
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in combination with metronomic cyclophosphamide and methotrexate in patients with HER-2 positive metastatic breast cancer

Abstract: Background: HER2/neu overexpression is linked to promotion of angiogenesis in breast cancer. We therefore tested the activity of the combination of Trastuzumab with metronomic, low dose chemotherapy with cyclophosphamide (CTX) and methotrexate (MTX) in metastatic breast cancer (MBC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 23 publications
(24 reference statements)
5
47
1
3
Order By: Relevance
“…In agreement to our findings, other promising results using MCT were obtained in patients with metastatic breast cancer treated with Cy plus Methotrexate (Mtx) [28], Cy plus Mtx and Thalidomide [29], Cy plus Mtx and Trastuzumab in Her2/neu+ patients [30]; besides, it was recently demonstrated that MCT with capecitabine displayed good therapeutic activity in advanced breast cancer [31]. Also, in patients with colorectal cancer at high risk of recurrence, adjuvant postoperative MCT using Irinotecan plus Uracil and Tegafur improved overall survival rates [32].…”
Section: Discussionsupporting
confidence: 78%
“…In agreement to our findings, other promising results using MCT were obtained in patients with metastatic breast cancer treated with Cy plus Methotrexate (Mtx) [28], Cy plus Mtx and Thalidomide [29], Cy plus Mtx and Trastuzumab in Her2/neu+ patients [30]; besides, it was recently demonstrated that MCT with capecitabine displayed good therapeutic activity in advanced breast cancer [31]. Also, in patients with colorectal cancer at high risk of recurrence, adjuvant postoperative MCT using Irinotecan plus Uracil and Tegafur improved overall survival rates [32].…”
Section: Discussionsupporting
confidence: 78%
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 54%
“…The goal of low-dose chemotherapy is to lessen the side effects of treatment and inhibit tumor growth, possibly through an antiangiogenic effect (20,34). In these studies, however, we exploited a new opportunity to use similarly low, clinically achievable levels of MTX (,10 mmol/L) to enhance the radiosensitivity of breast cancer cells to 111 In-NLS-trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab is commonly combined with taxane-or platinum-based chemotherapy regimes (27), but it was recently demonstrated that significant clinical benefit could be achieved in patients refractory to trastuzumab by combining the drug with oral low doses of cyclophosphamide and MTX (34). The goal of low-dose chemotherapy is to lessen the side effects of treatment and inhibit tumor growth, possibly through an antiangiogenic effect (20,34).…”
Section: Discussionmentioning
confidence: 99%